ASUHAN KEPERAWATAN GIGI DAN MULUT PADA PASIEN DIABETES MELITUS (LAPORAN KASUS) - Diyah Fatmasari; Muhammad Fiqih Sabilillah; Yodong , (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2015)
TITLEDental nursing care in diabetes mellitus patients (case report)ABSTRACTTo determine dental and oral health care, operators must be able to recognize the symptoms and signs possibility patients suffer systemic disease should be detected as these influence oral hygiene condition. Patients who often visit dental clinic are patients with diabetes mellitus. It is important for operator to know dental management of patients with diabetes melitus therefore diagnosis and treatment can be drawn as needed. Operator also can contribute dental health care and improve quality life of patients diabetes melitus by improving oral hygiene management and complication prevention. Purpose of this report to identify and understand dental and oral health care based on human need with behavior management for dental disease prevention.A diabetes melitus patient with caries occlusal 16 with diagnosis caries reach pulp visit dental clinic. Dental and oral health care to restore tooth shape and function, prevent further caries and reduce pain. Treatment for the patient was dental prophylaxis, dental health education and referral for root canal treatment. Evaluation need to be done regularly.Dental and oral health care are expected to be systematically so that the management of patients with diabetes mellitus can be continue. Dental management patient with diabetes melitus need good communication, laboratorium test and knowledge of operator about diabetes melitus including the effect of dental care, therefore diabetic patient can undergo dental care safety. Key words : Dental and Oral Health Care, Diabetic Patient